2020
DOI: 10.1002/job.2443
|View full text |Cite
|
Sign up to set email alerts
|

The passion bug: How and when do leaders inspire work passion?

Abstract: Summary Drawing from signaling theory, we propose a work passion transfer model where leaders' passion is transmitted to employees through the former's leadership style and is contingent on employees' perceived importance of performance to self‐esteem (IPSE). Data from 201 supervisor–employee dyads from the health‐care industry show that leaders' harmonious passion led to employees' harmonious passion through charismatic leadership, whereas contingent reward leadership accounted for the transfer of obsessive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 100 publications
2
56
1
1
Order By: Relevance
“…The current findings shed light on how being charismatic is associated with sexual desire and satisfaction in romantic relationships, which are key components of maintaining overall romantic relationship quality (Butzer & Campbell, 2008;Chau et al, 2011;Impett, Strachman, et al, 2008). Past research has found that charismatic people tend to be more communally oriented (Bass, 1985;Pillai et al, 2003) and passionate in workplace contexts (Ho & Astakhova, 2020), allowing for greater job and life satisfaction for both themselves (Nassif et al, 2020) and their colleagues (Ezez et al, 2008;Shamir et al, 1993;Vlachos et al, 2013). However, the current set of studies are the first to our knowledge to investigate the romantic relationships of charismatic people.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The current findings shed light on how being charismatic is associated with sexual desire and satisfaction in romantic relationships, which are key components of maintaining overall romantic relationship quality (Butzer & Campbell, 2008;Chau et al, 2011;Impett, Strachman, et al, 2008). Past research has found that charismatic people tend to be more communally oriented (Bass, 1985;Pillai et al, 2003) and passionate in workplace contexts (Ho & Astakhova, 2020), allowing for greater job and life satisfaction for both themselves (Nassif et al, 2020) and their colleagues (Ezez et al, 2008;Shamir et al, 1993;Vlachos et al, 2013). However, the current set of studies are the first to our knowledge to investigate the romantic relationships of charismatic people.…”
Section: Discussionmentioning
confidence: 60%
“…Given that charismatic people have been described as more communally oriented in a workplace setting through their emphasis on a collective identity (House & Howell, 1992;Shamir et al, 1993) and focus on other people's needs (Bass, 1985;Pillai et al, 2003), we CHARISMA AND SEXUAL QUALITY IN RELATIONSHIPS 20 suspected that charismatic people would be more communal in their romantic relationships, as well. More specifically, charismatic are often viewed as passionate (Ho & Astakhova, 2020) and desirable (Flegr et al, 2019), so we believed that charismatic people might be particularly likely to be high in sexual communal strength in their relationships. In fact, our studies revealed that charisma was associated with higher sexual communal strength, and this was true above and beyond general communal motivation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations